Brinjal grown in protected cultivation is safe for consumption - Singh, Priyanka; Singh, Balraj; Jethra, Geetika (Indian Horticulture, 2015)
Farmers can make good profit by selling the high quality vegetables in niche or upmarket of nearby cities. This technology will also open doors of new opportunities of employment for the youth of ruralareas.